2011
DOI: 10.1063/1.3530631
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and Raman Scattering in Ag-doped ZnO Nanoparticles

Abstract: Effects of Ag doping on the crystallinity and optical properties of zinc oxide (ZnO) nanoparticles have been studied by x-ray diffraction, diffuse reflectance spectroscopy, micro-Raman, and photoluminescence spectroscopy. It has been observed that while Ag-doping at low concentration improves the optoelectronic properties of ZnO nanostructures, Ag-doping at high concentrations drastically modify the emission behavior and lattice vibrational characteristics of the nanostructures. High Ag content in ZnO nanostru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
119
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(133 citation statements)
references
References 39 publications
13
119
0
1
Order By: Relevance
“…The incorporation of defects/impurity may breakdown of translational crystal symmetry [33,34] UV-Vis spectra were recorded from 200 to 800nm range and is as shown in Fig. S2.Ag-ZnO Nps (Fig.S2 (b).)…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of defects/impurity may breakdown of translational crystal symmetry [33,34] UV-Vis spectra were recorded from 200 to 800nm range and is as shown in Fig. S2.Ag-ZnO Nps (Fig.S2 (b).)…”
Section: Resultsmentioning
confidence: 99%
“…Such PL intensity variation in nanostructures with change in dopant concentration can be understood via considering the formation of different defects. 37 The UV peak is usually considered as the characteristic emission of ZnO and is attributed to the near band edge (NBE) exciton emission, which originates from free exciton (i.e., combination of electron and hole) luminance and a broad visible band observed due to formation of native defects across the band gap of ZnO. UV and Visible bands in undoped and doped ZnO have multiple emission and frequently assigned to differentiate defects.…”
Section: B Photoluminescence Spectroscopymentioning
confidence: 99%
“…4 shows room temperature Raman spectra of the as-prepared ZnO samples measured using 633 nm laser source at 10 mW power. Various researchers [30][31][32] reported that wurtzite ZnO belongs to the space group C 4 6ν with two formula units per primitive cell where all atoms occupy C 3ν sites. Also, it is well known that ZnO has eight sets of characteristic optical phonon modes at the center of Brillouin zone (Γ-point), which according to group theory [21,27,29] is predicted as:…”
Section: Photoluminescence (Pl) Analysismentioning
confidence: 99%
“…where A 1 and E 1 are two polar phonon modes, each comprising of longitudinal optical (LO) and transverse optical (TO) components, which are both Raman and IR active; E 2 is non-polar and only Raman active with two frequency modes: E 2 low (E 2L ) for Zn sublattice and E 2 high (E 2H ) for oxygen sublattice while B 1 modes are Raman inactive [30][31][32]. Strong E 2H mode is characteristic of wurtzite lattice and shows good crystallinity [30].…”
Section: Raman Spectroscopymentioning
confidence: 99%